EDUKASI SIKAP BERWIRAUSAHA DAN KETERAMPILAN BERWIRAUSAHA DALAM MENINGKATKAN PENJUALAN - Jonner Simarmata; Said Almaududi; Zuhri Saputra Hutabarat (Pengabdian Deli Sumatera, 2024)
This service aims to find out entrepreneurial attitudes, entrepreneurial skills and sales income in the Actual FKIP Canteen, Jambi University. Service activities were carried out for one month in March 2024. The service approach was carried out using level 1 action research, where actions related to solutions to problems identified or improvements made were not tested. This service was carried out in the Actual FKIP Canteen, Jambi University. The results of this service: 1) Can add concepts to the theory regarding the influence of entrepreneurial attitudes and entrepreneurial skills on sales income in the FKIP Actuanl Jambi University canteen, 2) As student input on the importance of the influence of entrepreneurial attitudes and entrepreneurial skills on sales income in the FKIP canteen Actual Jambi University. 3) Can be used as a guide or reference for subsequent similar assessments. It can be seen that there are many opinions and views regarding the dimensions of entrepreneurial skills. So the dimensions used for this research use opinion.